The challenge of customary law implementation in the optimistic law era in saving healthy Indonesian environment - Sembiring, Tamaulina Br.; Fitri, Lamhot Leonard; Holil, Holil; Siburian, Henry Kristian; Cakranegara, Pandu Adi (International research journal of management, IT and social sciences, 2022)
This study aims to gain understanding from several scientific publications to answer the problem, namely the challenges of implementing customary law in the unitary State of the Republic of Indonesia, which has favorable laws for saving a healthy Indonesian environment. The author believes that every implementation of the law, both customary Laws and others, certainly has obstacles and challenges in this republic of Indonesia regardless of the goal of saving the environment and other factors. So to prove it, we have reviewed as many as 56 publications to back up all of them in answering this problem. Before we get an answer, of course, we will examine the number of documents that we get by relying on a phenomenological approach, namely getting answers from a large number of data through studies such as coding evaluation data and data interpretation to get correct and valid answers to the study questions after discussing the data findings, where the challenges in implementing customary law are found that the existence of positive law is more substantial even though customary law has received legal provisions and decisions of the supreme court.